Investment guide for community-based seed entrepreneurs in cowpea production - Tolorunju, E.; Ayeni, F.; Adeniyi, R.; Silwal, P.K.; Faleti, O.; Archibong, B.; Shakiru, Q.; Ahmad, M.; Luwa, S. (International Institute of Tropical Agriculture, 2023)
This handbook is intended to guide seed farmers, entrepreneurs, agro-dealers, extension workers, students of agriculture, and researchers on the cost and return analysis of cowpea seed production in northeast Nigeria. The guide draws its lessons from the work and experience of IITA and partners in research for the development of seed systems in Nigeria. This publication is a production of the Feed the Future Nigeria Integrated Agriculture Activity implemented in targeted locations of Adamawa, Borno, Gombe, and Yobe states, Nigeria, between July 2019 and December 2024, and was made possible through funding support from the United States Agency for International Development (USAID). As part of its contribution to the economic recovery process in the northeast part of Nigeria, which the insurgent activities of armed groups have ravaged, USAID awarded the International Institute of Tropical Agriculture (IITA) and its partners (International Crops Research Institute for the Semi-Arid Tropics and Catholic Relief Services) the five and half-year “Feed the Future Nigeria Integrated Agriculture Activity’’. This aims to advance the objectives of inclusive and sustainable agriculture-led economic growth, strengthen resilience among people and systems, and support a well-nourished population, especially among women and children in the targeted locations of Adamawa, Borno, Gombe, and Yobe states in northeast Nigeria. The activity seeks to support vulnerable populations to engage in basic farming activities that will improve food security, increase agricultural incomes, and improve resilience among smallholder farmers and their families. It works with a coalition of partners to facilitate improved agro-inputs and extension advisory services to serve vulnerable populations; strengthens the institutions that form the market system and the networks that serve smallholder farmers who have been disenfranchised by conflict; and facilitates the engagement of youth and women in economic and entrepreneurial.